Fast and accurate prediction of drug induced proarrhythmic risk with sex specific cardiac emulators - Paula Dominguez-Gomez; Alberto Zingaro; Laura Baldo-Canut; Caterina Balzotti; Borje Darpo; Christopher Morton; Mariano Vázquez; Jazmin Aguado-Sierra (npj Digital Medicine)
Abstract In silico trials for drug safety assessment require many high-fidelity 3D cardiac simulations to predict drug-induced QT interval prolongation, which is often computationally prohibitive. To streamline this process, we developed sex-specific emulators for a fast prediction of QT interval, trained on a dataset of 900 simulations. Our results show significant differences between 3D and 0D single-cell models as risk levels increase, underscoring the ability of 3D modeling to capture more complex cardiac responses. The emulators demonstrated an average error of 4% compared to simulations, allowing for efficient global sensitivity analysis and fast replication of in silico clinical trials. This approach enables rapid, multi-dose drug testing on standard hardware, addressing critical industry challenges around trial design, assay variability, and cost-effective safety evaluations. By integrating these emulators into drug development, we can improve preclinical reliability and advance the practical application of digital twins in biomedicine.